Data from: Bidirectional adaptive introgression between two ecologically divergent sparrow species - Walsh, Jennifer; Kovach, Adrienne I.; Olsen, Brian Justin; Shriver, W. Gregory; Lovette, Irby J. (Dryad, 2018)
Natural hybrid zones can be used to dissect the mechanisms driving key
evolutionary processes by allowing us to identify genomic regions
important for establishing reproductive isolation and that allow for
transfer of adaptive variation. We leverage whole-genome data in a system
where two bird species, the saltmarsh (Ammospiza caudacutus) and Nelson’s
(A. nelsoni) sparrow, hybridize despite their relatively high background
genetic differentiation and past ecological divergence. Adaptive
introgression is plausible in this system because Nelson’s sparrows are
recent colonists of saltwater marshes, compared to the specialized
saltmarsh sparrow that has a longer history of salt-marsh adaptation.
Comparisons among whole-genome sequences of 34 individuals from allopatric
and sympatric populations show that ongoing gene flow is shaping the
genomic landscape, with allopatric populations exhibiting genome-wide FST
estimates close to double of that observed in sympatry. We characterized
patterns of introgression across the genome and identify regions that
exhibit biased introgression into hybrids from only one parental species.
These regions offer compelling candidates for genes related to tidal marsh
adaptations suggesting that adaptive introgression is an important
consequence of hybridization. These findings highlight the value of
considering the landscapes of both genome-wide introgression and
divergence when characterizing the evolutionary forces that drive
speciation.
Walsh et al. 2018_Evolution.RawSNPDataVCF containing variant data for 34
whole genomes analyzed in this study. These include allopatric
Nelson's sparrows (AlloNESP), allopatric saltmarsh sparrows
(AlloSALS), sympatric Nelson's sparrows (SymNESP), sympatric
saltmarsh sparrows (SymSALS), and one seaside sparrow used as an outgroup
(SESP). See methods for variant calling/filtering parameters.Walsh et al.
2018_Evolution_RawSNPData.vcf
Keywords: Ammospiza nelsoni; Ammospiza caudacutus